2017
DOI: 10.1016/j.athoracsur.2017.03.032
|View full text |Cite
|
Sign up to set email alerts
|

Conversion From Off-Pump Coronary Artery Bypass Grafting to On-Pump Coronary Artery Bypass Grafting

Abstract: Intraoperative conversion from OPCAB to ONCAB remains a morbid event with a risk of mortality much higher than expected. Surgeons should consider elective ONCAB in those with a high risk for conversion during OPCAB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 20 publications
0
25
0
1
Order By: Relevance
“…Arrhythmias and hypotension were two conditions observed causing conversions. In a recent analysis of STS Adult Cardiac Surgery Database (ACSD) involving over 196,000 patients reported that the conversion rate was 5.5% of which 50% were elective [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Arrhythmias and hypotension were two conditions observed causing conversions. In a recent analysis of STS Adult Cardiac Surgery Database (ACSD) involving over 196,000 patients reported that the conversion rate was 5.5% of which 50% were elective [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…In the previously cited meta‐analysis, emergency conversion raised the OR of mortality to 6.99 (95% CI, 5.18–9.45) 98. In addition to the noted increased mortality, IOC is also associated with increased risk of almost all perioperative complications including myocardial ischemic injury, stroke, renal failure, and prolonged ventilation 97, 100, 101. Furthermore, IOC is associated with increased costs102 as well as hospital readmissions and infectious complications 103.…”
Section: Intraoperative Conversion From Off‐pump To On‐pumpmentioning
confidence: 98%
“…In an analysis based on the STS ACSD, Keeling et al97 reported observed to expected mortality of 1.4 for an elective IOC, 1.6 for emergency IOC for visualization reasons, and 2.7 for emergency IOC for hemodynamic instability. In the previously cited meta‐analysis, emergency conversion raised the OR of mortality to 6.99 (95% CI, 5.18–9.45) 98.…”
Section: Intraoperative Conversion From Off‐pump To On‐pumpmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Society of Thoracic Surgeons database, the conversion rate for 196,000 patients was 5.5%, of which 50% were elective. 18 In the Randomized On/Off Bypass (ROOBY) trial, 11 the rate of conversion was 12.5% (surgeons took part regardless of their experience, and 55% of the procedures were performed by surgeons in training). Even in the CABG Off or On Pump Revascularization Study (CORONARY) trial, 10 in which surgeons were required to have performed 100 OPCAB procedures before been allowed to recruit, the conversion rate was 7.9%.…”
Section: Opcab: For the Many Or The Few?mentioning
confidence: 99%